Mercado de carbono como mecanismo de mitigação às mudanças climáticas: análise da produção científica brasileira - Tomadon, Ana Paula (2024)
Climate change has been a widely discussed topic over the past two decades, with global warming taking center stage in this debate. One of the key points in this discussion is that CO₂ is the main greenhouse gas responsible for this warming, and one instrument that has proven important in helping mitigate this situation is the carbon credit market. To understand how this market has contributed to mitigating climate change, particularly in Brazil, a bibliometric analysis was conducted by reviewing articles related to the topic, published in the Web of Science database, from 1997 to 2023. The study was structured in two stages: first, an attempt was made to identify the total number, the annual quantitative distribution, and the country of origin of the publications to understand the overall picture of studies worldwide in that database. In the second stage, Brazilian articles related to the topic were identified and analyzed, with a focus on the authors and journals with the highest volume of publications. Additionally, the subjects addressed in these articles were categorized using Lawrence Bardin's Content Analysis. The database search was conducted in the first half of 2024, and 24 articles on Brazil were found that relate to the keywords "climate change" and "carbon credits". Among the results, it was observed that a significant portion of Brazilian scientific production studies the generation of carbon credits from the contribution of forests. This survey allowed us to conclude that there is a significant opportunity for new studies to be developed by researchers considering other contexts of carbon credits, such as the energy sector, soil management, and coastal and marine ecosystems. It is believed that this survey can contribute to understanding a part of the scientific production on the topic and encourage new research approaches and carbon measurement methodologies to be developed in other contexts.